Relation between the Views and the Real Estate Application to a Mediterranean Coastal Area - Hugo Castro Noblejas; Jesús Vías Martínez; Matías F. Mérida Rodríguez (ISPRS International Journal of Geo-Information, 2022)
The landscape is a factor considered when choosing to purchase a dwelling, and, therefore, it influences the price of the real estate market. However, it is difficult to measure and assess its role, since it has a series of features that work in an integrated way and are hard to quantify separately. The characteristics of the views from each dwelling must also be considered, as well as their intrinsic characteristics or proximity to public services. This study proposes an automatic method to analyze the quality of the views, including both its dimensions and its composition in order to be able to estimate the economic weight of the views in the real estate value. A series of measurements of the views from 226 dwellings are integrated into the final index equation. The results are then compared with the estimated dwelling prices. The results highlight that the average price increases up to 18.1% in dwellings with a larger high-quality visual basin. It has also been noted that it is difficult to establish a correlation between the quality of the views and the housing prices due to the multifactorial nature of the housing prices.